If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -14 = 11x Reorder the terms: -14 + 7x = 11x Solving -14 + 7x = 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. -14 + 7x + -11x = 11x + -11x Combine like terms: 7x + -11x = -4x -14 + -4x = 11x + -11x Combine like terms: 11x + -11x = 0 -14 + -4x = 0 Add '14' to each side of the equation. -14 + 14 + -4x = 0 + 14 Combine like terms: -14 + 14 = 0 0 + -4x = 0 + 14 -4x = 0 + 14 Combine like terms: 0 + 14 = 14 -4x = 14 Divide each side by '-4'. x = -3.5 Simplifying x = -3.5
| -2x-4=24 | | -2(2x-6)=20 | | -2(x+5)=30 | | 2(2x-6)=40 | | 4x-2x+2=16 | | x-5x+4=-8 | | 2x+8x=17 | | -7x+5x+2=20 | | x-8-3=10 | | 8z=40 | | 24x-3=15+45x | | 9t=-16t^2+60t | | -13y-7y=-140 | | 2x-7=20+12x | | 13y-7y=-140 | | -10x-3x=-39 | | 3x+4y+z= | | -4x-8x=48 | | 60*0-30x=-180 | | c=a+ab | | 3a(n+7)=43 | | 60y-30x=-180 | | 3p^2+12p+11=0 | | 3(2x-3)=63 | | c=(a*b)+a | | 15x-15=3x-129 | | 12x+12=x+100 | | 2(x-2)(x+3)-(2x+4)(x-2)=0 | | -4x-8=48 | | 6x-14=49-2x | | 2(3x-4)=3x+28 | | 2(4x+5)=64-x |